(3GdGSJjYGH aj eYQaI GdCUMGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI HTjQ Hf HGdadSWjfi heGJ gh HYO SfI NeS hKeGfjf HTjQ Hf YeQh hdO ai YGe GdgLQI s
(3BNQgG (B:s
(3HGH MQedg Hf ghPI GdYGeQI bhe UMh CNhg NGdO Hf ghPg Ydi GdfHi Udi Gddg Ydjg hSde aSQ HgeG hgeG eYOhOGf ai GdeDda bdhHge s
(3GdfSNI HgG MhGTs
(3bWYI efgs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs